The relationship of topographical memory performance to regional neurodegeneration in Alzheimer's disease - Pengas, George; Williams, Guy; Acosta-Cabronero, Julio; Ash, Tom; Hong, Young; Izquierdo-Garcia, David; Fryer, Tim; Hodges, John; Nestor, Peter (Frontiers in Aging Neuroscience, 2012)
The network activated during normal route learning shares considerable homology with the network of degeneration in the earliest symptomatic stages of Alzheimer’s disease (AD). This inspired the Virtual Route Learning Test (VRLT) in which patients learn routes in a virtual reality environment. This study investigated the neural basis of VRLT performance in AD to test whether impairment was underpinned by a network or by the widely held explanation of hippocampal degeneration. VRLT score in a mild AD cohort was regressed against grey matter (GM) density and diffusion tensor metrics of white matter (WM) (n=30), and, cerebral glucose metabolism (n=26), using a mass univariate approach. GM density and cerebral metabolism were then submitted to a multivariate analysis (support vector regression) to examine whether there was a network associated with task performance. Univariate analyses of GM density, metabolism and WM axial diffusion converged on the vicinity of the retrosplenial/posterior cingulate cortex, isthmus and, possibly, hippocampal tail. The multivariate analysis revealed a significant, right hemisphere-predominant, network level correlation with cerebral metabolism; this comprised areas common to both activation in normal route learning and early degeneration in AD (retrosplenial and lateral parietal cortices). It also identified right medio-dorsal thalamus (part of the limbic-diencephalic hypometabolic network of early AD) and right caudate nucleus (activated during normal route learning). These results offer strong evidence that topographical memory impairment in AD relates to damage across a network, in turn offering complimentary lesion evidence to previous studies in healthy volunteers for the neural basis of topographical memory. The results also emphasize that structures beyond the mesial temporal lobe contribute to memory impairment in AD—it is too simplistic to view memory impairment in AD as a synonym for hippocampal degeneration.